New diabetes treatment by sulfonamides carbamides - Zegarra Araujo, Napoleón (1957)
Thirty-six years ago, researchers Frederick Banting and Best, of Toronto, able to isolate insulin from the pancreas and apply it to the treatment of diabetes, it is current, natural, fast-acting insulin; but this property of being fast action is that their management is laborious, requiring many injections a day and spends too much insulin, sowing distrust in some patients for accidents resulting. Then we have to solve the first problem insulinisation: Delaying the action of insulin, for which purpose it is associated to vasoconstrictors such as pituitary hormones and adrenaline, bringing its share to eight hours is prolonged, but endocrinologist that time as Umber, not supported as insulin reservoir and removed from therapeutic use.